Motivational Field of Creative Activities of the Population of the South of Russia Based on the Materials of Research in the Stavropol Territory - Anatolyevna Ivashova, Valentina; Borisovna Nadtochy, Yuliya; Sergeevna Budovich, Lidia; Valeryevna Volobuyeva, Evgeniya; Mikhailovna Volkova, Natalia (International Journal of Engineering and Technology, 2018)
The article considers the results of study of the motivational field, ensuring the participation of the population of the Stavropol Territory in amateur arts. The analysis of factors and conditions that contribute to the involvement of residents of the South of Russia in the creative activity on the basis of branch organizations of culture. The motivational sphere of professional activities of the heads of amateur groups of artistic creativity is considered as an important factor ensuring stable reproduction of positive social practices aimed at preserving the original cultural environment of the strategically important region of Russia.The study found that the stability of the composition of groups with a tendency to rejuvenation of participants is maintained; the main motive for citizens is the desire to engage in creativity (stated by every second participant of the survey), such motives as the desire to be seen, the ability to communicate, the impression of visiting the concert are also significant; the attractiveness of classes in the team of amateur arts is provided by active concert activities, the opportunity to speak to the public, regular rehearsal activities, cultural leisure, communication with people, spiritual growth and the opportunity to escape from everyday worries.Â Â